2020
DOI: 10.3847/1538-4357/ab7ffc
|View full text |Cite
|
Sign up to set email alerts
|

Massive Warm/Hot Galaxy Coronae. II. Isentropic Model

Abstract: We construct a new analytic phenomenological model for the extended circumgalactic material (CGM) of L * galaxies. Our model reproduces the OVII/OVIII absorption observations of the Milky Way (MW) and the OVI measurements reported by the COS-Halos and eCGM surveys. The warm/hot gas is in hydrostatic equilibrium in a MW gravitational potential, and we adopt a barotropic equation of state, resulting in a temperature variation as a function of radius. A pressure component with an adiabatic index of γ = 4/3 is inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 122 publications
6
57
0
Order By: Relevance
“…Fukugita & Peebles 2006) and has been confirmed by numerous observations (e.g. Anderson & Bregman 2011;Bogdán et al 2017;Li et al 2017;Faerman, Sternberg & McKee 2020) Our description of this gas phase is physically motivated as a stratified medium in hydrostatic equilibrium with the dark matter halo and is consistent with the current evidence from observations, which are, however, still limited and mostly reliable only for the inner parts of the haloes. We can see from Fig.…”
Section: Influence Of the Hot Gassupporting
confidence: 86%
“…Fukugita & Peebles 2006) and has been confirmed by numerous observations (e.g. Anderson & Bregman 2011;Bogdán et al 2017;Li et al 2017;Faerman, Sternberg & McKee 2020) Our description of this gas phase is physically motivated as a stratified medium in hydrostatic equilibrium with the dark matter halo and is consistent with the current evidence from observations, which are, however, still limited and mostly reliable only for the inner parts of the haloes. We can see from Fig.…”
Section: Influence Of the Hot Gassupporting
confidence: 86%
“…Our densities and temperatures also show good agreement, especially in the inner halo. Our pressure profile is lower than the Faerman et al (2020) model that also includes non-thermal sources of turbulent and magnetic/cosmic ray pressure. That model assumes HSE, but Oppenheimer (2018) showed that these low-z haloes are not well described by HSE in their inner CGMs, though at 0.5R 200 the thermal pressure gradient accounts for ≥ 75 per cent of the support against gravity (their fig.…”
Section: Hot Gas Radial Profilesmentioning
confidence: 64%
“…13), where photoionization becomes important. The importance of photoionization for the CGM ion content was previously pointed out by Faerman et al (2020) in their isentropic model of the CGM of an L * galaxy.…”
Section: Cie(t = T 200cmentioning
confidence: 72%